Peran Kantor Pertanahan Kota Batu dalam Pelaksanaan Program Percepatan Redistribusi dan Legislasi Tanah di Desa Tulungrejoa - Harisman, Harisman; Imron, Ali (Postgraduate University of Merdeka Malang, 2024)
Land within the territory of the Republic of Indonesia is one of the main resources, which, in addition to having profound intrinsic value for the Indonesian people, also serves a very strategic function in fulfilling the increasingly diverse and growing needs of the population. The city of Batu still possesses land that is state-owned, inherited from the Colonial Dutch era, which can be utilized for the welfare of Batu's citizens. Given this reality, the author has chosen the title